NLRP3 inflammasome in the pathogenesis of acute myocardial infarction: a cardiologist's view - V. V. Ryabov; A. E. Gombozhapova; Yu. O. Samoilova; M. A. Sirotina; D. A. Malysheva; L. N. Maslov (Российский кардиологический журнал)
Within five years after myocardial infarction (MI), a third of patients have secondary major adverse cardiovascular events (MACEs). The first randomized clinical trials to show the effectiveness of anti-inflammatory strategies in the prevention of MACEs are CANTOS, COLCOT and LoDoCo2. These studies have identified an effective therapeutic target — the NLRP3 inflammasome. The results of COLCOT and LoDoCo2 led to colchicine becoming the first anti-inflammatory drug to be included in clinical guidelines for the treatment of patients with coronary artery disease (CAD). However, considering colchicine in routine clinical practice requires the cardiologist to have knowledge of the basic molecular mechanisms of inflammation in cardiovascular diseases. The review discusses current data on inflammation and the NLRP3 inflammasome in the pathogenesis of CAD and MI, results and issues of their application in clinical cardiology.